Analysis of Understanding ond Strengthening Of Character Students Integration through Passages Qauliyah Course Materials on the Development of Animal - Arnentis Arnentis; Evi Suryawati (Universitas Sebelas Maret, 2015)
Research has been conducted conducted research to improve the understanding of students and strengthening the character through the integration of passages qauliyah on lecture material development of animals. This research is descriptive research that is focused on the integration of learning materials to strengthen the character through the study of passages qauliah set forth in the form of a paper-making tasks in subjects Animal Development held in Biology Education Studies Program, Department of Mathematics and Science Education at the University of Riau FKIP semester year 2014/2015 teachings. The subjects were students of Biology Education Program S1 are taking courses totaling Animals Developments 31 people. Research parameters measured in this study is the ability of students to integrate the value - the value of character include: religious, honest, disciplined, hard working, creative, independent, curiosity and duties in the form of a report in the form of paper. The result showed the depth of material is relatively good student it is seen by the results of student papers, 48.4% (15 people) of students scored on the category A, 45.2% (14 people) of students scored at the category B and only 6, 5% (2) category students studying material enough in the development of the selected animals. It shows more than 90% of students are able to explore and discuss the materials specified (in the form of verses kauniyah) to explore and integrate verses qauliyah (verse Al-Qur, an). Based on the results and discussion of this study concluded that understanding and strengthening the character of the students can through the integration of passages qauliyah with lecture material development of animals in Semester 2014/2015 in Biology Education Studies Program, Department of Mathematics and Science Education FKIP Riau UniversityKeywords: reinforcement, character, verses qauliah, materials, development of animals